Transarterial Radioembolization for Hepatocellular Carcinoma in Korea: Current Clinical Practices, Facility Requirements, and Patient Selection - Dongho Hyun (Journal of the Korean Society of Radiology)
Before initiating Yttrium-90 (90Y) radioembolization, both the interventional radiology and nuclear medicine departments must prepare facilities for radionuclide handling, implement appropriate radiation protection and monitoring measures, and ensure that all medical personnel possess the required government-issued certification. According to current guidelines, transarterial radioembolization is recommended as an alternative treatment option for patients with a single hepatocellular carcinoma measuring ≤8 cm and classified as stage I, II, or III according to the modified Union for International Cancer Control staging system. However, these indications may be adjusted based on the institution’s medical clinical setting and resources. Given the potential for irreversible tissue damage from 90Y, treatment efficacy and safety must be assessed through planning angiography and either planar imaging or SPECT-CT using 99mTc-macroaggregated albumin.